2020
DOI: 10.1098/rsos.200649
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour and habitat-use drives niche segregation in sibling seabird species

Abstract: To mediate competition, similar sympatric species are assumed to use different resources, or the same but geographically separated resources. The two giant petrels ( Macronectes spp.) are intriguing in that they are morphologically similar seabirds with overlapping diets and distributions. To better understand the mechanisms allowing their coexistence, we investigated intra- and interspecific niche segregation at Marion Island (Southern Indian Ocean), one of the few localities where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 77 publications
(136 reference statements)
1
16
0
Order By: Relevance
“…A good example of where the first hypothesis (H1) has been used to explain sexual segregation is in the dimorphic, scavenging giant petrels Macronectes spp. The larger, dominant males have been observed to directly exclude females from seal and penguin carcasses on land, forcing females to primarily forage at‐sea (Gonzalez‐Solis et al., 2000; but see discussions in Granroth‐Wilding & Phillips, 2019 and Reisinger et al., 2020 that demonstrated more behavioural flexibility than previously thought for these species). Social dominance and competitive exclusion have also been suggested to explain sexual segregation in polygynous species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A good example of where the first hypothesis (H1) has been used to explain sexual segregation is in the dimorphic, scavenging giant petrels Macronectes spp. The larger, dominant males have been observed to directly exclude females from seal and penguin carcasses on land, forcing females to primarily forage at‐sea (Gonzalez‐Solis et al., 2000; but see discussions in Granroth‐Wilding & Phillips, 2019 and Reisinger et al., 2020 that demonstrated more behavioural flexibility than previously thought for these species). Social dominance and competitive exclusion have also been suggested to explain sexual segregation in polygynous species.…”
Section: Discussionmentioning
confidence: 98%
“…The two main hypotheses commonly used to explain sexual segregation in central place foragers are (H1) competitive exclusion (through direct competition) or (H2) niche divergence (through indirect competition, Phillips et al, 2004).A good example of where the first hypothesis (H1) has been used to explain sexual segregation is in the dimorphic, scavenging giant petrels Macronectes spp. The larger, dominant males have been observed to directly exclude females from seal and penguin carcasses on land, forcing females to primarily forage at-sea(Gonzalez-Solis et al, 2000; but see discussions in Granroth-Wilding &Phillips, 2019 andReisinger et al, 2020 that demonstrated more behavioural flexibility than previously thought for these species).…”
mentioning
confidence: 98%
“…Marine predators, such as seabirds, face different constraints during the breeding and non-breeding seasons. Most seabirds breed in colonies and foraging is confined to a restricted radius around this central place owing to the need to return to the nest to care for offspring, which may lead to high intra- and interspecific competition between individuals and species [ 20 , 21 ]. Once breeding is over and central place constraints are relaxed one would expect sympatric species with similar resource requirements to disperse into the wider environment at low densities and intermix as resource limitation and competition will be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The null hypothesis was rejected if the overlap calculated from the observed data was significantly different from the overlap calculated from a simulated dataset (1000 permutations) in which breeding state (breeder and nonbreeder) was randomly assigned to individuals during each breeding stage. Significance ( p values) was estimated as the proportion of permuted overlap scores that were smaller than the observed overlap (e.g., Botha & Pistorius, 2018; Reisinger et al, 2020). The p values calculated from Monte Carlo permutations are approximations and are thus given with 95% confidence intervals.…”
Section: Methodsmentioning
confidence: 99%